2016
DOI: 10.1111/tri.12736
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival outcomes between Expanded Criteria Donor and Standard Criteria Donor kidney transplant recipients: a systematic review and meta-analysis

Abstract: SUMMARYIn 2002, the United Network for Organ Sharing proposed increasing the pool of donor kidneys to include Expanded Criteria Donor (ECD). Outside the USA, the ECD definition remains the one used without questioning whether such a graft allocation criterion is valid worldwide. We performed a meta-analysis to quantify the differences between ECD and Standard Criteria Donor (SCD) transplants. We paid particular attention to select studies in which the methodology was appropriate and we took into consideration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 49 publications
3
52
1
1
Order By: Relevance
“…The recent evolution in recipient demographics and expansion of the donor pool have introduced several important variables that may contribute to the lack of improvement in longterm allograft survival but may be better matched with predicted patient survival [4][5][6][7]. Although the changes in the kidney allocation scoring system have led to presumed improved equity in organ availability for disadvantaged recipients, the transplant community is in need of an objective measure to aid in determining which patients are at the highest risk for graft failure [5][6][7][8]. Implementation of an easy, cost-effective measure that can be utilized during routine lab review to target patients for intervention is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The recent evolution in recipient demographics and expansion of the donor pool have introduced several important variables that may contribute to the lack of improvement in longterm allograft survival but may be better matched with predicted patient survival [4][5][6][7]. Although the changes in the kidney allocation scoring system have led to presumed improved equity in organ availability for disadvantaged recipients, the transplant community is in need of an objective measure to aid in determining which patients are at the highest risk for graft failure [5][6][7][8]. Implementation of an easy, cost-effective measure that can be utilized during routine lab review to target patients for intervention is needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to kidneys retrieved from standard donors, ECD and DCD organs show higher rates of primary failure (PNF) and delayed graft function (DGF) [3][4][5][6]. Inferior renal function and higher discard rates have been also highlighted by several reports.…”
Section: Introductionmentioning
confidence: 94%
“…In an attempt to expand the donor pool and match the increasing amount of patients in the waiting lists, the transplant community has more recently moved from the traditional boundaries set by the standard donation after brain death (DBD) toward the new frontiers of expanded criteria donors (ECD) [2,3] and donation after cardiac death (DCD) [4,5]. However, compared to kidneys retrieved from standard donors, ECD and DCD organs show higher rates of primary failure (PNF) and delayed graft function (DGF) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Querar et al published a meta‐analysis with a comparison of survival outcomes between ECD and SCD kidney transplant recipients. The authors concluded that patient‐graft survival, patient survival, and death‐censored graft survival were worse in the ECD group . Considering the longer life expectancy in younger patients, this result should be taken into account.…”
Section: Expanded Criteria Donormentioning
confidence: 99%